131k views
1 vote
If g(x) = x^3-x+1,find a) g(0)b) g(-1) c) g(1)

1 Answer

3 votes

To answer this question, we have to substitute the corresponding value of x into the function to obtain the values of the function for each given point.

Then if we have that the function is:


g(x)=x^3-x+1

Then we have:

For x = 0:


\begin{gathered} g(0)=(0)^3-(0)+1 \\ g(0)=1 \end{gathered}

For x = -1:


\begin{gathered} g(-1)=(-1)^3-(-1)+1 \\ g(-1)=-1+1+1 \\ g(-1)=1 \end{gathered}

For x = 1:


\begin{gathered} g(1)=(1)^3-(1)+1 \\ g(1)=1-1+1 \\ g(1)=1 \end{gathered}

In summary, therefore, we have that:


\begin{gathered} g(0)=1 \\ g(-1)=1 \\ g(1)=1 \end{gathered}

User Rhodee
by
5.3k points